A Free Boundary Problem Arising from the Leaching of Saline Soils - Knabner, Peter (SIAM Journal on Mathematical Analysis, 1986)
A multidimensional parabolic free boundary problem of the implicit type arises in models in the soil sciences. Existence, uniqueness and asymptotic behaviour of weak and classical solutions are considered.<br
Keywords: free boundary problems; parabolic boundary problems; nonlinear parabolic systems; parabolic systems; parabolic systems of degenerate type